(untitled) (KYAMC Journal, 2025)
We describe a case of a 19-year-old Bangladeshi woman who was diagnosed with 19 weeks of missed abortion. Before admission to our hospital, she received medical and mechanical induction of abortion in a health complex. On admission to the obstetric ward of our hospital, her ultrasound revealed a 19-week non-viable pregnancy. After repeated medical and mechanical induction having no desirable result we decided on dilatation and curettage (D&C). As D&C failed to evacuate any product of conception laparotomy was done. During this procedure, a left-sided unruptured rudimentary horn pregnancy with a non-viable fetus was discovered. The horn was surgically resected. The patient was sent home after a smooth postoperative recovery. In advanced gestation, rudimentary horn pregnancy is extremely rare and frequently cannot be distinguished from an intrauterine pregnancy. For rudimentary horn pregnancy, first-trimester ultrasonography is by far the only noninvasive, sensitive diagnostic technique available. The gold standard of therapy for advanced rudimentary horn pregnancy continues to be laparotomy with horn removal. The failure of repeated induction compelled us to perform a laparotomy, and we explored a rare condition, the failure of management of which could certainly lead to a catastrophic event. KYAMC Journal. 2024; 15(02): 105-107